RETRACTED: Collective emotions of the university staff in the context of digital learning - Polyushkevich O.A.; Chuvashova M.N.; Zhuravleva I.A.; Komarova M.V.; Zavarzina Yu.V. (E3S Web of Conferences)
See the retraction notice E3S Web of Conferences 420, 00001 (2023), https://doi.org/10.1051/e3sconf/202342000001